1976
DOI: 10.1007/bf00313487
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological findings in the syndrome of acute ocular muscle palsy with ataxia (fisher syndrome)

Abstract: 4 patients are described with ophthalmoplegia (Figs. 1 and 2) and ataxia with acute onset. Three of them showed only very slight symptoms of generalized polyneuritis. Measurement of sensory nerve conduction velocity (Fig. 4, Table 2) and determination of vibration sense by an electrical vibrator (Fig. 3) proved to be helpful for diagnosis. The ocular EMG revealed signs of peripheral denervation in 3 cases. Pathological changes of the somatosensory evoked potential (Fig. 5) which has been registered in one case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 4 publications
0
11
1
Order By: Relevance
“…These findings suggest a block of conduction in the spinal roots, limb girdle plexuses or proximal segments of the nerves. Several reports had the consensus that sensory changes predominated with significant loss of amplitudes and mild motor and sensory conduction slowing [21, 22, 25, 26, 29]. In our study, this phenomenon was not observed.…”
Section: Discussioncontrasting
confidence: 36%
See 3 more Smart Citations
“…These findings suggest a block of conduction in the spinal roots, limb girdle plexuses or proximal segments of the nerves. Several reports had the consensus that sensory changes predominated with significant loss of amplitudes and mild motor and sensory conduction slowing [21, 22, 25, 26, 29]. In our study, this phenomenon was not observed.…”
Section: Discussioncontrasting
confidence: 36%
“…As the result reported by Shuaib and Becker [19], all of the antecedent events in our patients were URTI only. Gastrointestinal infection, which was the second common one reported by other series [20, 21], was not present in our patients. In contrast to the previous report [18], the commonest initial symptom in our patients was dizziness (6/11, 54.5%) rather than diplopia (table 2).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The days listed in the nerve conduction studies (NCSs) column indicate the timing of the NCSs from the onset of FS. Abbreviations: URI: upper respiratory infection case series indicate that demyelinating processes cause the decreased amplitudes of SNAPs observed in patients with FS (11)(12)(13)(14), whereas the results from two large case series suggest that axonal neuropathy or dorsal root ganglionopathy are responsible (8,10). Therefore, the question of whether decreases in SNAP amplitudes result from a demyelinating process or an axonal mechanism remains controversial.…”
Section: Introductionmentioning
confidence: 99%